2022
DOI: 10.1186/s12951-021-01201-y
|View full text |Cite|
|
Sign up to set email alerts
|

Homologous targeting nanoparticles for enhanced PDT against osteosarcoma HOS cells and the related molecular mechanisms

Abstract: Background No prominent advancements in osteosarcoma (OS) treatment have been made in the past 20 years. Although photodynamic therapy (PDT) is an emerging technique for cancer therapy, the lack of targeted photosensitizers for OS treatment severely limits its applications. Results In this study, we constructed a potential theranostic nanoplatform by using (poly (lactic-co-glycolic) acid (PLGA) nanoparticles (NPs) encapsulating IR780 into the shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 65 publications
(68 reference statements)
0
40
0
Order By: Relevance
“…Innate lesion-homing capabilities of CM provide excellent drug delivery and multimodal diagnosis across varied fields, including cancer, immune diseases, and infectious diseases. For instance, integration of different mechanisms such as immunotherapy, light therapy, and ferroptosis can overcome tumor resistance (Wang et al., 2022b ). Notably, the bionic system with an increased surface area upon the coating on PLGA core is more conducive for exposure and stretching of antigen or receptor-binding protein and shows great talents in immunoregulation, anti-inflammatory, pathological molecular blockade, and nanosponge detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Innate lesion-homing capabilities of CM provide excellent drug delivery and multimodal diagnosis across varied fields, including cancer, immune diseases, and infectious diseases. For instance, integration of different mechanisms such as immunotherapy, light therapy, and ferroptosis can overcome tumor resistance (Wang et al., 2022b ). Notably, the bionic system with an increased surface area upon the coating on PLGA core is more conducive for exposure and stretching of antigen or receptor-binding protein and shows great talents in immunoregulation, anti-inflammatory, pathological molecular blockade, and nanosponge detoxification.…”
Section: Discussionmentioning
confidence: 99%
“… MH-PLGA-IR780 NPs theranostic nanoplatform-guided PDT approach could contribute to PDT-mediated apoptosis and inhibit tumor growth in mouse xenografts. [ 173 ] PTT The mPDA NPs core endowed the mPDA@CMs NPs-CQ with good photothermal capability to mediate PTT killing of prostate cancer cells, while NIR-triggered CQ release from the nanosystem further arrested PTT-induced protective autophagy of cancer cells, thus weakening the resistance of prostate cancer cells to PTT. The mPDA@CMs NPs-CQ could induce significant autophagosome accumulation, ROS generation, mitochondrial damage, endoplasmic reticulum stress, and apoptotic signal transduction, which finally results in synergistic prostate tumor ablation in vivo.…”
Section: Pdt And/or Ptt Combined With Immunotherapymentioning
confidence: 99%
“…Zhang et al have used sinoporphyrin sodium to study cholangiocarcinoma and confirmed that PDT alone downregulates the expression of the cystine/glutamate transporter (system x c -), thus inducing ferroptosis [41]. In addition, to enhance the therapeutic effect, Wang et al have used a polylactic acid-glycolic acid copolymer to load the photosensitizer IR780 (Figure 2) [42]. The micelle nanoparticles were then coated with human osteosarcoma cell membranes to obtain a biomimetic active targeting nanoplatform (MH-PLGA-IR780).…”
Section: Mono-pdt and Pdt-induced Ferroptosismentioning
confidence: 99%